Analisis Empiris Atas Teori Dualistik Ekonomi Lewis: Studi Kasus Indonesia: IPB University, International Center for Applied Finance and Economics (Inter CAFE). - Hubbansyah, Aulia Keiko; Dedi Budiman Hakim; Sri Hartoyo; Widyastutik (IPB University, 2023)
Indonesia’s economic development is marked by changes in the structure of the economy and employment from those originally based on agriculture to non-agriculture, which is called structural transformation. This study discusses the turning point phenomenon in employment which is one of the important theses in the dualistic economic development analysis framework formulated by Lewis (1954). Related to changes in the sectoral employment structure and the achievement of turning points, this study finds that Indonesia has not yet entered a turning point stage. The achievement of Lewis’s turning point in Indonesia tends to be temporary. Viewed from the decomposition of sectoral growth, the contribution of the non-agricultural sector to economic growth is two times greater than that of the agricultural sector. This shows that economic growth in Indonesia is strongly driven by the role of the non-agricultural sector. This study also found that layers of labor from the agricultural to non-agricultural sectors had a positive impact on economic growth in Indonesia.